2017
DOI: 10.1021/acs.energyfuels.7b01781
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of CO Methanation for the Production of Synthetic Natural Gas in a Fluidized Bed Reactor

Abstract: In order to obtain the characteristics of the CO methanation process, numerical simulations are carried out in a fluidized bed reactor. The model is validated by comparing the simulation results of the gas composition with experimental data. The influences of the operational parameters on H 2 conversion and CH 4 yield are evaluated. The CO conversion and selectivity of CH 4 increase with rising pressure but decrease with rising temperature. The increase of the catalyst inventory leads to difficulty in removing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…41 The deposited carbon was confirmed by the XRD patterns, and as seen in Figure 11b, two small diffraction peaks that appeared around 40°belong to Ni Previous studies have reported that the catalytic performance of Ni-based catalysts is influenced by the grain size of Ni particles and the Ni electron density. 31,42 First, according to the XRD and H 2 -TPD results, the outstanding activity of the Ni/La x Ce 1−x O 2−x/2 catalyst was due to the smallest Ni particle size, which contributes to the formation of more active sites as well as increasing H 2 uptakes, ultimately improving the CO methanation activity. 33,43 Second, the Ni electron cloud density was increased for the Ni/La x Ce 1−x O 2−x/2 catalyst, as shown in XPS spectra, which could be considered as the increased number of oxygen vacancies derived from the formation of La−Ce−O linkages.…”
Section: Resultsmentioning
confidence: 99%
“…41 The deposited carbon was confirmed by the XRD patterns, and as seen in Figure 11b, two small diffraction peaks that appeared around 40°belong to Ni Previous studies have reported that the catalytic performance of Ni-based catalysts is influenced by the grain size of Ni particles and the Ni electron density. 31,42 First, according to the XRD and H 2 -TPD results, the outstanding activity of the Ni/La x Ce 1−x O 2−x/2 catalyst was due to the smallest Ni particle size, which contributes to the formation of more active sites as well as increasing H 2 uptakes, ultimately improving the CO methanation activity. 33,43 Second, the Ni electron cloud density was increased for the Ni/La x Ce 1−x O 2−x/2 catalyst, as shown in XPS spectra, which could be considered as the increased number of oxygen vacancies derived from the formation of La−Ce−O linkages.…”
Section: Resultsmentioning
confidence: 99%
“…4 ) and Reaction 2 ( Eq. (5) ): ( Er-rbib and Bouallou, 2013 ; König et al, 2015 ; Sun et al, 2017 ) where Rate constants K 1 ( Eq. 6 ) and K 2 ( Eq.…”
Section: Experimental Methodology and Techniquesmentioning
confidence: 99%
“…The temperature should be well controlled in order to guarantee both kinetic rate and production rate. From the simulations and References [9,16,22], the optional temperature should be between 350 • C and 400 • C.…”
Section: Influence Of Initial Temperaturementioning
confidence: 99%